The role of hybridization and introgression in maintaining species integrity and cohesion in naturally isolated inselberg bromeliad populations. (9th October 2018) - Mota, M. R.; Pinheiro, F.; Leal, B. S. S.; Wendt, T.; Palma‐Silva, C.
Abstract: Hybridization is a widespread phenomenon present in numerous lineages across the tree of life. Its evolutionary consequences range from effects on the origin and maintenance, to the loss of biodiversity. We studied genetic diversity and intra‐ and interspecific gene flow between two sympatric populations of closely‐related species, Pitcairnia flammea and P. corcovadensis ( Bromeliaceae ), which are adapted to naturally fragmented Neotropical inselbergs, based on nuclear and plastidial DNA. Our main results indicate a strong reproductive isolation barrier, although low levels of interspecific gene flow were observed in both sympatric populations. The low rates of intraspecific gene flow observed for both P. corcovadensis and P. flammea populations corroborate the increasing body of evidence that inselberg bromeliad species are maintained as discrete evolutionary units despite the presence of low genetic connectivity. Nuclear patterns of genetic diversity and gene flow revealed that hybridization and introgression might not cause species extinction via genetic assimilation of the rare P. corcovadensis . In the face of reduced intraspecific gene exchange, hybridization and introgression may be important aspects of the Pitcairnia diversification process, with a positive evolutionary impact at the bromeliad community level, and thus contribute to increasing and maintaining genetic diversity in local isolated inselberg populations.